Social isolation alters central nervous system monoamine content in prairie voles following acute restraint. (4th March 2018) - McNeal, Neal; Anderson, Eden M.; Moenk, Deirdre; Trahanas, Diane; Matuszewich, Leslie; Grippo, Angela J.
ABSTRACT: Animal models have shown that social isolation and other forms of social stress lead to depressive- and anxiety-relevant behaviors, as well as neuroendocrine and physiological dysfunction. The goal of this study was to investigate the effects of prior social isolation on neurotransmitter content following acute restraint in prairie voles. Animals were either paired with a same-sex sibling or isolated for 4 weeks. Plasma adrenal hormones and ex vivo tissue concentrations of monoamine neurotransmitters and their metabolites were measured following an acute restraint stressor in all animals. Isolated prairie voles displayed significantly increased circulating adrenocorticotropic hormone levels, as well as elevated serotonin and dopamine levels in the hypothalamus, and potentially decreased levels of serotonin in the frontal cortex. However, no group differences in monoamine levels were observed in the hippocampus or raphe. The results suggest that social stress may bias monoamine neurotransmission and stress hormone function to subsequent acute stressors, such as restraint. These findings improve our understanding of the neurobiological mechanisms underlying the consequences of social stress.